Firm Size As A Moderating Variable On Audit Delay Factors Analysis - Putra, I Made Ryan Ananta; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p06, 2024)
Companies that go public avoid audit delays. This refers to the OJK rule number 29/POJK.04/2016 and the size effect phenomenon. This study aims to determine the impact of firm size as a moderating variable of the relationship between profitability and leverage on audit delay in food and beverage companies on the Indonesia Stock Exchange. The study used a purposive sampling technique and obtained a sample of 49 observations from 2014-2020. Applying moderated regression analysis, the results indicate firm size could not moderate the relationship between the effect of profitability on audit delay and firm size could positively moderate the relationship between leverage and audit delay. In other words, the results of this study encourage companies that have a good image in the public to try to avoid audit delays by strengthening their internal controls. Keywords: Audit Delay; Food and Beverage; Profitabilitas; Leverage; Firm Size